Implementasi Konsep “New Art Gudeg” pada Interior Pusat Informasi dan Sentra Kuliner Makanan Tradisional di Yogyakarta - Felicia Natalie Tjoanda; Laksmi Kusuma Wardani; David Tan Kayogi (Intra, 2019)
Yogyakarta has many potential cultural, educational and tourist developments. One of the tourism potentials in Yogyakarta is culinary tourism. Interior Design Information Center and Culinary Center for Gudeg Traditional Yogyakarta Food provides information center and culinary center facilities that can be used to educate the surrounding community, and are supported by other facilities such as lobby, workshop, ATM Center, and office area. The concept applied in this design is